1999
DOI: 10.1126/science.284.5412.316
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Morphogenesis But Intact IKK Activation in Mice Lacking the IKKα Subunit of IκB Kinase

Abstract: The oligomeric IkappaB kinase (IKK) is composed of three polypeptides: IKKalpha and IKKbeta, the catalytic subunits, and IKKgamma, a regulatory subunit. IKKalpha and IKKbeta are similar in structure and thought to have similar function-phosphorylation of the IkappaB inhibitors in response to proinflammatory stimuli. Such phosphorylation leads to degradation of IkappaB and activation of nuclear factor kappaB transcription factors. The physiological function of these protein kinases was explored by analysis of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
605
6
5

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 781 publications
(648 citation statements)
references
References 33 publications
32
605
6
5
Order By: Relevance
“…The DNp51B-dominant condition achieved by targeting IKKa shows hyperplasia with concomitant increase of undifferentiated keratinocytes (Hu et al, 1999;Takeda et al, 1999). TAp51B transgenic mice suffer from epidermal hyperplasia and poor differentiation (Koster et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The DNp51B-dominant condition achieved by targeting IKKa shows hyperplasia with concomitant increase of undifferentiated keratinocytes (Hu et al, 1999;Takeda et al, 1999). TAp51B transgenic mice suffer from epidermal hyperplasia and poor differentiation (Koster et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that targeted mutations or misexpression of many genes, such as p63 (Mills et al, 1999;Yang et al, 1999), IKB kinase a subunit (Hu et al, 1999), and integrin (Raghavan et al, 2000), could cause absent or abnormal skin formation (reviewed in Yamanishi, 1998). The relationship between Fgfr2 signals and these factors are important topics for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the sequence similarity of IKKa and IKKb, the analysis of single knockout mice for these kinases has established that Rel/NF-kB activation by proinammatory cytokines is dependent largely on IKKb, whereas IKKa induces Rel/NF-kB during skin and skeletal development in response to an unidenti®ed morphogenetic signal(s). ikka 7/7 mice Mice homozygous for an ikka null mutation die post-natally, a icted with multiple morphological defects, the most striking of which is the encasement of the embryo in a shiny taut skin that prevents the emergence of fore-and hind-limbs (Hu et al, 1999;Takeda et al, 1999). Other defects include an absence of ears, truncation of the head and snout, and skeletal abnormalities a ecting the vertebrae, sternum, skull and digital phalanges that arise from the absence or inappropriate fusion of bones.…”
Section: Null Mutations For the Ikb Kinasesmentioning
confidence: 99%
“…Nevertheless, evidence of a role for Rel/NF-kB factors in vertebrate limb and skin development has previously come from over-expressing mutant IkBa in chick embryos (Bushdid et al, 1998;Kanegae et al, 1998) and in the dermis of transgenic mice (Seitz et al, 1998). The normal induction of Rel/NF-kB in ikba 7/7 embryonic ®broblasts in response to the pro-inflammatory cytokines TNFa or IL-1 occurs via IKKb (Hu et al, 1999;Takeda et al, 1999), and this ®nding suggests that an unknown set of signals operating through IKKa is required for the induction of Rel/NFkB during skin and skeletal development.…”
Section: Null Mutations For the Ikb Kinasesmentioning
confidence: 99%
See 1 more Smart Citation